The Legal Strength of Notary Actions in the Implementation of Parate Execution towards Responsibility & Execution Rights to Fidusian Objects - Ilham Syam (Sultan Agung Notary Law Review, 2020)
This research aims to: to find out howthe legal force of the notary deed in the application of the execution parate of the right of collateral and the parate of execution of the fiduciary object. The approach method in this research is empirical normative, the data source is obtained from the literature and the legal materials used are primary, secondary and tertiary legal materials which are then analyzed by means of qualitative analysis. Based on the results of data analysis, it can be concluded that the material rights fiduciary provides guarantees. The collateral object is tangible, intangible and immovable movable object which cannot be guaranteed with a mortgage. Fiduciary security is widely used by financing companies. The debtor in default, the leasing party executes the fiduciary object unilaterally, this is considered contrary to the 1945 Constitution. Article 15 paragraph (2) and Article 15 paragraph (3) Law No. 42 of 1999 concerning Fiduciary Guarantee is subject to a judicial review. Formulation of the problem, how the execution of fiduciary guarantees after the decision of the Constitutional Court No. 18 / PUU- XVII / 2019. Research method, using library research in the form of secondary data. This research is juridical normative and qualitative research type. The discussion after the decision of the Constitutional Court No. 18 / PUU-XVII / 2019 states that Article 15 paragraph (2) and Article 15 paragraph (3) of Act No. 42 of 1999 are contrary to the 1945 Constitution. Conclusion, before the Constitutional Court decision the execution of the object of fiduciary guarantee based on Article 29 of the Act No. 42 of 1999 concerning Fiduciary Guarantee. After the Decision of the Constitutional Court No. 18 / PUU-XVII / 2019 states that the collateral execution cannot be carried out unilaterally by the creditor, but must go through a decision of the District Court, unless there is an agreement regarding the default between the debtor and the creditor and the debtor voluntarily submits the object of fiduciary collateral.